PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS NASKAH DRAMA SATU BABAK SISWA KELAS VIII SMP NEGERI 30 PADANG - Wasilah, Tri; R., Syahrul; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACTÂ The purpose of this research is to explain the effect of cooperative learning of think pair share type to writing skill in class VIII at Junior High School 30 Padang. The kind of this research is quantitative research with experiment metode. The results of the research there are three. First, the skills of writing a one-act drama script grade VIII SMP Negeri Padang 30 without the use of cooperative learning model types think pair share qualification enough (C) with an average value of 61,82. Second, the skills of writing a one-act drama script grade VIII SMP Negeri Padang 30 by using cooperative learning model types think pair share is on the qualifications of either (B) with an average value of 82,32.Â Third, based on the t-test results, it was concluded that the alternative hypothesis (H1) received on the standard of 95% and dk = (n1 + n2)-2 due tcount > ttable (9,32 > 1,67).Â Kata kunci: pengaruh model pembelajaran kooperatif tipe think pair share, menulis naskah drama satu babak